The process of reconciliation: evaluation of guidelines for translating quality-of-life questionnaires. (April 2012) - Koller, Michael; Kantzer, Valeska; Mear, Isabelle; Zarzar, Katie; Martin, Mona; Greimel, Eva; Bottomley, Andrew; Arnott, Maria; Kuliśś, Dagmara
Reconciliation refers to the process through which two or more independent forward translations are merged into one single translation. This critical step in the translation process is difficult to formalize. The purpose of this review is to analyze how reconciliation is specified in leading guidelines for the translation of quality-of-life questionnaires and other patient-reported outcome forms with regard to the number and qualifications of individuals involved, the processes followed, as well as the criteria applied. In general, relatively little attention has been paid to characterizing the process in detail. Based on these findings, we specify criteria to be followed.